Prevalence of Opportunistic Infections and its Treatment in Patients with HIV Infection in a South Indian Tertiary Care Hospital - ST, Elizabeth; N, Kiran (Indian Journal of Pharmacy Practice)
The rapid spread of Human Immunodeficiency Virus (HIV) or Acquired Immunodeficiency Syndrome (AIDS) in India is a cause for great and increasing concern. The management of opportunistic infections (OIs) is an essential component of comprehensive HIV/AIDS treatment and care. Our study is a hospital based retrospective observational study conducted on 244 HIV patients who were admitted in a South Indian tertiary care hospital during the period between January 2011-12. We retrieved required data from patient case records from the medical record department of the Antiretroviral Therapy (ART) centre and documented in a patient profile form, specifically designed for our study. The age distribution pattern inferred that the percentage of men infected with HIV was higher 148 (61%) than females 96 (39%). In the age distribution pattern the age group of 30-39 years included the highest number of patients 114 (46%), followed by the age group 40-49 years with 61 patients (25%). The most common opportunistic infections were oropharyngeal candidiasis in 92 (37.7%) patients followed by tuberculosis in 72 (29.5%). We observed adverse drug reactions like Zidovudine (AZT) induced anaemia in 21 patients (8.6%). The most widely administered combination of drugs for treating HIV was Zidovudine (AZT) + Lamivudine (3TC) + Nevirapine (NVP) in 129 (52.8%) patients. In the treatment of OI, Co-trimoxazole was used extensively in 213 patients (87.2%), Fluconazole was used in 124 patients (50.8%) and Albendazole in 112 patients (45.9%). Anti-tubercular drugs were used in 72 patients (29.5%). Hence, in our study we found that the most commonly detected OI is oral candidiasis followed by tuberculosis in HIV patients.
Keywords: Acquired Immunodeficiency Syndrome (AIDS); Antiretroviral Therapy (ART); Opportunistic infections (OI)